The Routledge handbook of Spanish history
1 online resource
Keywords: "This handbook offers comprehensive coverage of the history of Spain, exploring key themes and events in four broad but not necessarily rigid temporal categories: medieval, early modern, nineteenth century and twentieth century. Making the latest research in Spanish history more widely accessible to an international audience, The Routledge Handbook of Spanish History is an essential reference point for students and scholars of Spain, as well as those working in comparative European history"--